FORMULASI KODE ETIK PENDIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Farhan, Moh. (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
BeingÂ  EducatorÂ  is an honour profession in Islam. It is an essensial factor in the education system. Thus a dignityÂ  and an authority of this profession have to be maintained by the educators. The way to keep the honour of this profession can be done by conductingÂ  ethical codes as a guidence to conduct activities as the educators.In a modern era, an educator ethic has been formulated. However, it shows unoptimal to keep the educatorsâ€™ dignity. Thus, a solution is needed to solve the problem. Part of the solutionÂ  from Islamic education scholars during Islamic education hystory is the genuin thinking of those scholars.Â They have formulated the educatorâ€™s ethics codes. From their thinking and ideas, there are three ethic codes that can be understood: The First:Â  related to the obligation to have a good intention as the educator by improving a quality ofÂ  â€œtaqwaâ€ to Allah SWT because teaching is a worship. The second:Â  the educators have to keep theirÂ  profession by improving the personality with a good character (Akhlak). The third,Â  keep improving the educatorsâ€™ competences and professionalism.